PTU-314 Quality improvement project looking at inpatient acute gastrointestinal bleeds and ppi prescribing. (22nd June 2015) - Samuel, M; Thompson, C; Emms, J; Holt, C; Higham, D
Abstract : Introduction: Inpatient acute upper gastrointestinal bleeds (AUGIB) are associated with a high mortality rate. The use of PPI therapy can reduce the incidence of these bleeds. We aimed to examine all inpatient AUGIB and observe the prescribing practices leading upto them. Method: Data was collected on all patients that had an OGD following an inpatient AUGIB from January to June 2013. Mode of presentation, co morbidities, and medication on admission and post endoscopy were analysed. Results: 91 inpatient AUGIB were identified. The median age was 68 of which 50 males and 41 females were identified. Mean length of time from admission to AUGIB was 12 days. The modes of presentation were malaena (60%), coffee ground vomit (35%) and anaemia (5%). Relevant co –morbidities include alcohol excess (45%), gastritis (23%), previous ulcer disease (22%) and IHD/ACS (10%). 21 AUGIB (23%) might have been prevented; 16% (15/21) had their PPI stopped whilst on antibiotics. Of the 15 patients who had their PPI stopped whilst on antibiotics 73% (11/15) were over the age of 75 and had multiple co morbidities. Furthermore 7% (6/21) which might have been prevented were on high dose dual antiplatelet therapy. 50% of them were over the age of 75 and not on a PPI. Post OGD all 21 patients who potentially may have been prevented from bleeding were commenced on a PPI. Conclusion: 23% of inpatient AUGIB may have been prevented with adherence to appropriate prescribing practice and correct risk stratification. We have developed a new tool to assess AUGIB risk. Disclosure of interest: None Declared.